Hybrid Heuristics for the Multi-stage Capacitated Lot Sizing and Loading Problem - Linet, Özdamar (STOCKTON PRESS, HOUNDMILLS, BASINGSTOKE RG21 6XS, HAMPSHIRE, ENGLAND, 1999)
The multi-stage capacitated lot sizing and loading problem (MCLSLP) deals with the issue of determining the lot sizes of product items in serially-arranged manufacturing stages and loading them on parallel facilities in each stage to satisfy dynamic demand over a given planning horizon. It is assumed that regular time capacity decisions have already been made in the tactical level and allocated to the stages, but it is still an important decision problem whether to augment regular time capacity by overtime capacity. Each item may be processed on a technologically feasible subset of existing facilities with different process and setup times on each facility. Since the solution of the MCLSLP requires the design of a powerful algorithm, simulated annealing (SA) and genetic algorithms (GA) are integrated to enhance their individual performances. Furthermore, these global optimisation methods are incorporated into a Lagrangean relaxation scheme, hence creating a hybrid solution methodology. Numerical results obtained using these methods confirm the mutual benefits of integrating different solution techniques.
Keywords: Heuristics; Simulated Annealing; Genetic Algorithms; Lagrangean Relaxation; Multi-stage Lot Sizing; Sezgiseller; Isıl İşlem; Genetik Algoritmalar; Lagrange Rahatlama; Çok Aşamalı Parti Büyüklüğü